Determinan Kepuasan Kerja Berdasarkan Pengembangan Karier Dan Keseimbangan Kehidupan Kerja - Surijadi, Herman; Tousalwa, Carla Carolien; Amin, Muhamad; Matakita, Muhajir; Musa, Muhammad Nur Deny; Muspiha, Muspiha; Siwabessy, Dominggus Jacobus (Journal of Economics Review (JOER), 2023)
This study aims to test and analyse the impact of career development and work-life balance on job satisfaction of bank employees in Ambon City. The approach in this research is included in quantitative research. The research model is a survey model using an online questionnaire instrument. The population in the study was all bank employees in Ambon City with the census technique as the sampling technique. Data analysis used multiple linear regression preceded by frequency distribution analysis of respondents' answers, classical assumption testing (normality, multicollinearity and heteroscedasticity tests) and research instrument testing (validity and reliability tests). The research findings prove that career development and work-life balance factors have a positive and significant impact on job satisfaction of bank employees in Ambon City